Persepsi dan partisipasi masyarakat terhadap pelestarian hutan mangrove di Kecamatan Bantan-Bengkalis - Novia Parenri; Sukendi Sukendi; Tengku Nurhidayah (Pelantar Press, 2018)
This study aims to determine the effect of community characteristics (age, education and income) and perceptions to the public participation in mangrove forest conservation, with research sites in two villages in the district of Bantan Bengkalis. Collecting data using a survey method with questionnaires and sampling was done by random sampling where the population 2494 people, which is used as the sample is taken as 97 respondents. The method of analysis used in this research is statistical descriptive and path analysis. And based on the results of statistical analysis has been done, obtained some results as follows: that of the community characteristics variable (age, education and income) only educational variables that have a significant direct effect on the public participation variable and also found that the perception variables have a significant directl effect on the public participation variable. Furthermore, the results also found that the public participation variables have a significant directl effect on the mangrove forest conservation variables.